Biodiversity and distribution patterns of free-living nematodes communities in Ba Lai river, Ben Tre province - Thai, Tran Thanh; Lam, Nguyen Le Que; Yen, Nguyen Thi My; Vanreusel, Ann; Quang, Ngo Xuan (Vietnam Journal of Science and Technology, 2018)
Nematodes communities in Ba Lai river, Ben Tre province were investigated in September of 2015 (eight stations from estuary to upstream). The results showed that the nematodes communities have characterized by high density and biodiversity, providing useful information of nematodes assemblages in freshwater habitas, in particular inland river. Also the results indicated that the distribution of nematodes communities in Ba Lai river was strongly discriminated between in and outside of dam with two groups. The Ba Lai dam may be reasons for cause  the nematodes distribution discontinuity. Present study is a pioneering attempt to record the impact of the dam on benthic-invertebrate in Vietnam.